Accountability in International Governance and the 2030 Development Agenda. Issue 3 (10th March 2016) - Ocampo, José Antonio; Gómez‐Arteaga, Natalie
Abstract: After revisiting the concept of accountability in national governance, this paper analyzes the challenges of its application to international governance, including an assessment of some of the modalities it has assumed. It then proposes a bottom‐up multilayered and multistakeholder accountability framework for the 2030 Development Agenda: national follow‐up processes at the base of the pyramid, consultations and possibly peer reviews at the regional level, a global accountability system led by the High‐Level Political Forum (HLPF) and supported by the ECOSOC system, United Nations and other international organizations, and active participation by civil society and the private sector with their own accountability frameworks in place. Abstract : It is essential that such accountability go beyond the usual concept of Corporate Social Responsibility and gradually include an evaluation of how core business practices contribute to development –and not only through the social and environmental footprint